2018
DOI: 10.5021/ad.2018.30.5.566
|View full text |Cite
|
Sign up to set email alerts
|

The Suppressive Effect of Butyrate and Bromopyruvate on Inflammatory Cytokine Production and Short Chain Fatty Acid Receptor Expression by Blood Mononuclear Cells in Patients with Behçet's Disease

Abstract: Background: Controlling inflammation is a therapeutic goal of various autoimmune/autoinflammatory diseases including Behçet's disease (BD). The immunomodulatory effect of metabolites or metabolic analogs such as butyrate and 3-bromopyruvate has been observed in animal disease models. Objective: We attempted to evaluate the effect of butyrate and 3-bromopyruvate on the inflammatory cytokine production by peripheral blood mononuclear cells (PBMCs) isolated from patients with mucocutaneous involvement of BD. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…We used much lower amounts of BrPA (20, 80, and 200 μM), as we wanted to examine the therapeutic potential of BrPA against Candida infection at the concentration that minimized human cell death. Our previous study found slightly decreased cell survival of peripheral blood mononuclear cells at 80 μM of BrPA 40. In this study, we demonstrated that both 80 and 200 μM of BrPA synergistically enhanced cell death in C. albicans (Figure 10), thus revealing the potential of the combination of AgNPs and BrPA as an antifungal agent against C. albicans .…”
Section: Discussionsupporting
confidence: 66%
“…We used much lower amounts of BrPA (20, 80, and 200 μM), as we wanted to examine the therapeutic potential of BrPA against Candida infection at the concentration that minimized human cell death. Our previous study found slightly decreased cell survival of peripheral blood mononuclear cells at 80 μM of BrPA 40. In this study, we demonstrated that both 80 and 200 μM of BrPA synergistically enhanced cell death in C. albicans (Figure 10), thus revealing the potential of the combination of AgNPs and BrPA as an antifungal agent against C. albicans .…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, a diet change might not have been the primary factor altering the abundance of B. uniformis in the gut microbiota during BD disease activity shift. Given our previous observation that SCFA negatively affects the production of inflammatory cytokines in patients with BD [ 46 ], we speculated an alteration in the abundance of SCFA producers during BD disease activity shift. Our findings do not concord with this speculation, but rather show an alteration in B. uniformis abundance, suggesting a possible role of the gut microbiome in BD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Crohn’s disease ( 29 , 30 ), rheumatoid arthritis (RA) ( 31 ), and ulcerative colitis ( 32 ) have significantly reduced amounts of E. rectale , and these patients have lower butyrate concentrations in their feces than healthy individuals. Butyrate treatment downregulated IL-6 in peripheral blood mononuclear cell cultures of patients with BD ( 33 ) and the downregulation of IL-6 was associated with BD symptom improvement in mice ( 34 ). Metagenomics studies have shown that the gut microbiota is associated with human diseases ( 35 ).…”
Section: Introductionmentioning
confidence: 99%